Aplikasi Pengelompokan Penjualan Dengan Clustering Data Mining Pada Toko Retail Kota Padang - Eka Praja Wiyata Mandala; Musli Yanto; Dewi Eka Putri (Ikatan Ahli Informatika Indonesia, 2018)
Retail is one or more activities that add value to the product to the consumer either for family needs or for personal use. Retail can sell products depending on current market needs. The goods we enjoy today are not apart from retail services, retail helps producers / distributors and consumers so that every need will be fulfilled. In this problem the author tries to do retail store research in the city of Padang. Retail store in question is minimarket. This study aims to assist retail stores in grouping the sale of goods. Data mining can be a solution in overcoming the problem. By using Clustering Data Mining, retailers will be able to classify the sales of goods in their retail stores. The results of the grouping gives an idea to the retail manager to be able to determine what items need to be held for the future. Applications are born this will not only be able to do the grouping process that occurs in this retail store alone, but it can also be penetrated into all aspects of retail both retail goods and retail services. This application can help to determine the procurement of goods in the sales process that will minimize the losses that occur in every sales activity.